Latin American Neostructuralism : The Contradictions of Post-Neoliberal Development - Leiva, Fernando Ignacio (Book collections on Project MUSE., 2008)
This landmark work is the first sustained critique of Latin American neostructuralism, the prevailing narrative that has sought to replace "market fundamentalism" and humanize the "savage capitalism" imposed by neoliberal dogmatism. Fernando Leiva analyzes neostructuralism and questions its credibility as the answer to the region's economic, political, and social woes. Recent electoral victories by progressive governments in Latin America promising economic growth, social equity, and political democracy raise a number of urgent questions, including: What are the key strengths and weaknesses of.